Proflie of Human β-Defensins 1,2 and Proinflammatory Cytokines (TNF-α, IL-6) in Patients with Chronic Kidney Disease - Dong-Jin Oh; Hye Ryoun Kim; Mi-Kyung Lee; Yo Seop Woo (Karger Publishers, 2013)
Background/Aim: Our aim was to determine whether altered human β-defensin (HBD), pro-inflammatory cytokines including interleukin (IL)-6 and tumor necrotic factor (TNF)-α could increase the risk of developing and exacerbation of chronic kidney disease (CKD), especially for patients with diabetic nephropathy (DN). Methods: Serum samples were obtained from 338 CKD patients and 88 sex, age-matched healthy controls. The concentrations of HBD-1 were assayed using an RIA kit. Serum levels of HBD-2, IL-6 and TNF-α were assayed using an ELISA kit. Results: Serum levels of HBD-1, IL-6 and TNF-α were significantly higher in CKD patients compared to healthy controls (Pβ = -0.357, P = 0.035) explaining the variability in HBD-1 in CKD. Diabetic nephropathy (DN) patients at stage 3-5 had significantly higher serum HBD-1 levels than non DN patients (P=0.00). Conclusion: Our data support the view that there is increased inflammation in CKD and DN. The inverse correlation between eGFR and serum HBD-1 which we observed is suggestive of a relationship between innate immunity and renal function and should be further investigated.